MOLDOVAN AGRI-FOOD SECTOR DILEMMA: EAST OR WEST? - Stratan, Alexandru (Economics of Agriculture, 2014)
During the period 2010-2013, Republic of Moldova launched a number of initiatives to develop the trade policy in order to ensure a more facilitating legal framework for the implementation of economic and trade relations with the key external partners. An agreement on the creation of a free trade area in the CIS was signed in this period. Similarly, Republic of Moldova started negotiating the Association Agreement with the European Union, which was signed in June this year and is part of the Deep and Comprehensive Free Trade Agreement (DCFTA). This article aims to assess the main effects of signing the Association Agreement for the Moldovan agricultural sector, while examining its reaction, if Moldova would have opted for integration within the Customs Union - Russian Federation, Belarus, and Kazakhstan.